A non-invasive method for silencing gene transcription in honeybees maintained under natural conditions - Franco Nunes, Francis Morais [UNESP]; Paulino Simoes, Zila Luz (Pergamon-Elsevier B.V. Ltd, 2009)
in the Apis mellifera post-genomic era, RNAi protocols have been used in functional approaches. However, sample manipulation and invasive methods such as injection of double-stranded RNA (dsRNA) can compromise physiology and survival. To circumvent these problems, we developed a non-invasive method for honeybee gene knockdown, using a well-established vitellogenin RNAi system as a model. Second instar larvae received dsRNA for vitellogenin (dsVg-RNA) in their natural diet. For exogenous control, larvae received dsRNA for GFP (dsGFP-RNA). Untreated larvae formed another control group. Around 60% of the treated larvae naturally developed until adult emergence when 0.5 mu g of dsVg-RNA or dsGFP-RNA was offered while no larvae that received 3.0 mu g of dsRNA reached pupal stages. Diet dilution did not affect the removal rates. Viability depends not only on the delivered doses but also on the internal conditions of colonies. The weight of treated and untreated groups showed no statistical differences. This showed that RNAi ingestion did not elicit drastic collateral effects. Approximately 90% of vitellogenin transcripts from 7-day-old workers were silenced compared to controls. A large number of samples are handled in a relatively short time and smaller quantities of RNAi molecules are used compared to invasive methods. These advantages culminate in a versatile and a cost-effective approach. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: Apis mellifera; Honey bee; Vitellogenin; RNAi feeding; Gene knockdown; Development; Non-invasive method; Off-target effects; Environmental RNAi